2010
DOI: 10.3402/meo.v15i0.5151
|View full text |Cite
|
Sign up to set email alerts
|

Working with interpreters: how student behavior affects quality of patient interaction when using interpreters

Abstract: BackgroundDespite the prevalence of medical interpreting in the clinical environment, few medical professionals receive training in best practices when using an interpreter. We designed and implemented an educational workshop on using interpreters as part of the cultural competency curriculum for second year medical students (MSIIs) at David Geffen School of Medicine at UCLA. The purpose of this study is two-fold: first, to evaluate the effectiveness of the workshop and second, if deficiencies are found, to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Thirteen articles focused on the language barriers affecting clinical care. [108][109][110][111][112][113][114][115][116][117][118][119][120] Five of the interventions were longitudinal, seven of these interventions were 1-3 h, and one was two and a half weeks. Eight out of the 13 interventions were mandatory.…”
Section: Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen articles focused on the language barriers affecting clinical care. [108][109][110][111][112][113][114][115][116][117][118][119][120] Five of the interventions were longitudinal, seven of these interventions were 1-3 h, and one was two and a half weeks. Eight out of the 13 interventions were mandatory.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Nevertheless, one article found that almost 40% of students failed to use interpreters in an encounter with a patient of limited English proficiency. 111 Zanetti et al 115 described a 4-year program that promotes cultural competency through civic engagement and second language fluency. Students who participated reported greater confidence in obtaining a medical history in a different language, advocating for the healthcare needs of underserved populations, and assessing the health beliefs and practice of patients from other cultures.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Previous research on strategies for interpreted communication mainly relate to the access to professional interpreters [31] , use of relatives or bilingual care providers as interpreters [8] or underutilisation of trained interpreters [32] . Other studies report organizational strategies such as recruitment of medically trained interpreters, co-operation between interpreter agencies and health care services and interpreter service integrated in the health care organization [18,19] or training health care professionals in interpreted communication [20] . In the present study, we did not estimate the use of professional interpreters or ad hoc interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to perform high-quality interpretation, the language service needs to be integrated into organisational routines [19] . Training health care professionals in working with interpreters has been shown to increase the use of interpreter services as well as maintaining patient-centeredness when the clinical encounter involves an interpreter [20] , and the quality of communication during the clinical encounter [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is incumbent on training institutions to educate training healthcare practitioners in working with interpreters. The literature suggests that few clinicians receive such training (Fung, Lagha, Henderson, & Gomez, 2010).…”
Section: Interpreters In Mental Health Carementioning
confidence: 99%